ANALISIS IMPLEMENTASI KEWIRAUSAHAAN SOSIAL DALAM PROGRAM KLINIK SUNGAI UNIVERSITAS CIPUTRA - Maria Satya Rani; Monika Teguh (BBM (Buletin Bisnis & Manajemen), 2016)
The complex problems in Indonesia require the people initiative to help the government in finding the solution. Thus arise a movement calls social entrepreneurship to identify and solve society problems in large scale. This movement uses the principles of business, but instead of profit oriented it is more social value oriented. Universitas Ciputra Surabaya also performs social entrepreneurship through the "River Clinic" program. This program aims to preserve Sungai Mas as the main water source for Surabaya. The implementation of the program was analized based on the social entrepeneurship principles. The research result is hoped to be some suggestion for the program improvement, so that it can be more significantly affected the Surabaya people. Keywords: entrepreneurship, social entrepreneurship, social entrepreneurship implementation, river clinic program